Factors influencing disease phenotype and penetrance in HFE haemochromatosis. - Rochette, J; Le Gac, G; Lassoued, K; Férec, C; Robson, K (2010)
Haemochromatosis is predominantly associated with the HFE p.C282Y homozygous genotype, which is present in approximately 1 in 200 people of Northern European origin. However, not all p.C282Y homozygotes develop clinical features of haemochromatosis, and not all p.C282Y homozygotes even present abnormal iron parameters justifying venesection therapy. This situation was not apparent from initial genotype/phenotype correlation studies as there was a selection bias of patients. Only those patients with a significant iron burden were included in these early studies. It is now largely accepted that the p.C282Y/p.C282Y genotype is necessary for the development of HFE haemochromatosis. However, this genotype provides few clues as to why certain symptoms are associated with the disease. Expression of iron overload in people with this genotype depends on the complex interplay of environmental factors and modifier genes. In this review, we restrict our discussion to work done in humans giving examples of animal models where this has helped clarify our understanding. We discuss penetrance, explaining that this concept normally does not apply to autosomal recessive disorders, and discuss the usefulness of different biochemical markers in ascertaining iron burden. Hepcidin, a peptide synthesized primarily by the liver, has been identified as the central regulator in iron homeostasis. Consequently, understanding its regulation is the key. We conclude that the main goal now is to identify important modifiers that have a significant and unambiguous effect on iron storage.